2016
DOI: 10.1016/j.smim.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing adoptive T cell immunotherapy with microRNA therapeutics

Abstract: Adoptive T cell-based immunotherapies can mediate complete and durable regressions in patients with advanced cancer, but current response rates remain inadequate. Maneuvers to improve the fitness and antitumor efficacy of transferred T cells have been under extensive exploration in the field. Small non-coding microRNAs have emerged as critical modulators of immune system homeostasis and T cell immunity. Here, we summarize recent advances in our understanding of the role of microRNAs in regulating T cell activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 130 publications
(210 reference statements)
2
26
0
1
Order By: Relevance
“…Consistent with our study, increasing evidence has demonstrated that extracellular miRNAs play critical roles in the development, differentiation and function of a variety of immune cells, including B and T lymphocytes, dendritic cells, and macrophages . The ability of miRNAs to target multiple molecules in signalling pathways and their involvement in regulating various aspects of T‐cell biology make them attractive molecules to exploit for more effective adoptive T‐cell therapies .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our study, increasing evidence has demonstrated that extracellular miRNAs play critical roles in the development, differentiation and function of a variety of immune cells, including B and T lymphocytes, dendritic cells, and macrophages . The ability of miRNAs to target multiple molecules in signalling pathways and their involvement in regulating various aspects of T‐cell biology make them attractive molecules to exploit for more effective adoptive T‐cell therapies .…”
Section: Discussionsupporting
confidence: 90%
“…Role of exosomal miR-24 in immune regulation of nasopharyngeal carcinoma 339 in regulating various aspects of T-cell biology make them attractive molecules to exploit for more effective adoptive T-cell therapies [31,32].…”
Section: Role Of Exosomal Mir-24 In Immune Regulation Of Nasopharyngementioning
confidence: 99%
“…However, trafficking, survival, and persistence of reinfused T cells need to be optimized, and genetic engineering of T cells is an approach currently explored to improve T-cell qualities. In particular, genetic manipulation of specific microRNAs may allow improvement of T-cell fitness (5). microRNAs are $22nt long noncoding RNAs that posttranscriptionally regulate protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…A deficiency of Dicer in T cells leads to the dysregulation of CD8 + T cell activation, proliferation and survival, indicating that miRNAs are major gene regulators during CD8 + T cell responses [28]. Therefore, the properties of miRNAs may be particularly relevant for the long-term survival of adoptively transferred T cells [29]. Extensive studies have indeed provided a comprehensive view of the expression and functionality of several [30,31].…”
Section: Biological Characteristics Of Mirnas In Cd8 + T Cellsmentioning
confidence: 99%